1985
DOI: 10.1172/jci112048
|View full text |Cite
|
Sign up to set email alerts
|

Treatment with aldose reductase inhibitor or with myo-inositol arrests deterioration of the electroretinogram of diabetic rats.

Abstract: Biochemical abnormalities in the retinal pigment epithelium of experimentally diabetic animals include increased sorbitol and decreased myo-inositol. Diabetes also causes a progressive reduction in the amplitude of the c-wave of the electroretinogram of the pigmented rat. The c-wave is generated by the retinal pigmented epithelium. Myo-inositol administration or treatment with sorbinil, an inhibitor of aldose reductase, arrested the decline in the c-wave. Therefore, hyperglycemia-associated defects in myo-inos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
25
0

Year Published

1988
1988
2000
2000

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(26 citation statements)
references
References 18 publications
1
25
0
Order By: Relevance
“…The relative abundance of aldehyde reductase (AR1) and AR2 mRNA was quantitated by filter hybridization of RNA from several human retinal pigment epithelial cell lines exposed to hyperglycemic and hyperosmolar conditions in vitro. AR2 but not AR1 mRNA was significantly increased some 11-to 18-fold by hyperosmolarity in several retinal pigment epithelial cell lines. A single cell line with a 15-fold higher basal level of AR2 mRNA than other cell lines tested demonstrated no significant increase in AR2 mRNA in response to hypertonic stress.…”
Section: Introductionmentioning
confidence: 94%
See 1 more Smart Citation
“…The relative abundance of aldehyde reductase (AR1) and AR2 mRNA was quantitated by filter hybridization of RNA from several human retinal pigment epithelial cell lines exposed to hyperglycemic and hyperosmolar conditions in vitro. AR2 but not AR1 mRNA was significantly increased some 11-to 18-fold by hyperosmolarity in several retinal pigment epithelial cell lines. A single cell line with a 15-fold higher basal level of AR2 mRNA than other cell lines tested demonstrated no significant increase in AR2 mRNA in response to hypertonic stress.…”
Section: Introductionmentioning
confidence: 94%
“…The RPE cell layer exhibits sorbitol accumulation, MI depletion, and impaired Na+/ K+-ATPase activity in diabetic rabbits (16,17). Moreover, electroretinographic impairment in diabetic pigmented rats is ascribed to dysfunction of the RPE cell layer and is corrected by either aldose reductase inhibitors (ARI) or by MI supple-mentation (18 ). Therefore, cultured RPE cells from a variety of mammalian species including humans have been examined as an in vitro model of biochemical and functional defects that may contribute to the pathogenesis of some diabetic complications in vivo (19,20).…”
Section: Introductionmentioning
confidence: 99%
“…However, the mechanism of action of aldose reductase inhibitors in diabetic neuropathy is not understood. On the other hand, it has been previously reported that aldose reductase inhibitors can improve ERG abnormalities in rats with diabetes (MacGregor & Matschinsky, 1985;Segawa et al 1988;Hotta, Kakuta, Fukasawa, Ando, Miyake, Awaya & Sakamoto, 1990) and galactosaemia (Segawa et al 1988), but the ERG parameters used in some of these studies were different from those employed here. The shape of the b-wave of the ERG, which we chose as the parameter for the present study, is related to hyperglycaemic metabolic dysfunction of the retinal Muller cells (Tamai & Tanaka, 1973;Deneault, Kozak & Danowski, 1980;Kozak et al 1983).…”
Section: Discussionmentioning
confidence: 65%
“…MacGregor and Matschinsky [9] found that Sorbinil arrested the progressive decrease of the c-wave in diabetic rats. Kozak et al [10] found that Sorbinil therapy started at the outset of diabetes in rats prevented the decline in amplitudes and increase of latencies in the a-waves and oscillatory potentials of untreated diabetic rats.…”
Section: Discussionmentioning
confidence: 96%